Drivers of Consumer Purchase Intention Toward Life Insurance: Mediating Role of Persuasion - Gurung, Grishma; Ojha, Aarati; Kharel, Sagar; Simkhada, Babita (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: By developing an integrated model grounded in behavioral economics, this study examines the key factors influencing consumer purchasing intentions towards life insurance through the mediation of persuasion.Design/methodology/approach: This study employed an explanatory research design, collecting cross-sectional data from 307 respondents in Kathmandu Valley conveniently through KoboToolbox. SmartPLS 4.0 was used to examine the structural relationship.Findings: Findings revealed that attitude, subjective norms, and saving motives significantly influence life insurance purchase intention, while risk aversion and financial literacy do not exhibit significant direct effects. Similarly, mediation analysis indicates that persuasion plays a critical role by significantly mediating the effects of subjective norms, attitude, saving motives, and financial literacy on purchase intention.Conclusion: These results highlight the centrality of psychosocial drivers and persuasive communication in shaping consumer behavior in Nepal’s life insurance sector.Implications: By identifying the behavioral levers that drive purchase intention and the persuasive pathways through which these levers operate, this study aspires to reposition life insurance not merely as a product but as a behavioral commitment to long-term security in an increasingly uncertain world. Originality/value: This study provides valuable empirical insights and novel perspectives by integrating behavioral factors and persuasion to explain life insurance purchase intention in Nepal’s emerging market context.JEL Classification: D12, G22, M31